A combination of naproxen and esomeprazole: Analgesic therapy on balancing cardiovascular and gastrointestinal risks - Andrei Evgenyevich Karateev; L I Alekseeva; S G Anikin (Современная ревматология)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are the most important tool to control pain in rheumatic diseases; however, their application is limited by the risk of serious complications in the cardiovascular system and gastrointestinal tract (GIT). The advent of a Russian new drug that is a naproxen and esomeprazole combination (Vimovo™) extends the possibilities of NSAIDS use. This review considers the benefits of both NEC components. The former is naproxen, a traditional NSAIDS that is in common use as an effective analgesic worldwide. Its chief merit is the least cardiovascular risk among all NSAIDs (aside from aspirin). Esomeprazole is a representative of the group of proton pump inhibitors, a potent antisecretory drug that has passed major tests as an agent for the prevention of NSAID-related GIT complications. This drug combination allows patient incompliance to gastroprotective therapy to be eliminated. Large-scale clinical trials have confirmed a considerable reduction in the frequency of GIT complications with NSAIDS use as compared to the standard enteric-coated naproxen, including in patients receiving low-dose aspirin. Comparison of NEC with celecoxib has indicated that the new medication is as effective as a selective COX-2 inhibitor in both efficacy and GIT safety.